Comparison of the Antibacterial Activity of Chelating Agents Using the Agar Diffusion Method - Jr., A. Hinton; Ingram, K.D. (International Journal of Poultry Science, 2010)
The agar diffusion assay was used to examine antibacterial activity of 2 metal chelators. Concentrations of 0-40 mM of ethylenediaminetetraacetic acid (EDTA) and ethylenediamine-N,N=-disuccinic acid (EDDS) were prepared in 1.0 M potassium hydroxide (KOH). The pH of the solutions was adjusted to 11.0 with citric acid and wells in agar media seeded with bacterial isolates were filled with the solutions. Agar plates were incubated at 35oC for 18-24 h and zones of inhibition around the agar wells were measured. Results indicated that 10 mM EDTA produced significant (p